KAJIAN PENDIDIKAN AGAMA ISLAM (PAI) DALAM PERSPEKTIF SOSIO-HISTORIS: Kebijakan dan Pengembangan Tatanan Sistem Pendidikan Nasional - Faridah, Faridah (Moderation | Journal of Islamic Studies Review, 2023)
An independent Indonesia means that it must manage itself in order to build and explore allits potential, both its natural wealth and most importantly the development of the potential of its entirehuman resources, which in the end is for the welfare of the Indonesian people based on Pancasila. Moreimportantly, aligning the dignity of the nation with the world community. Islamic education strongly supportsprogress and development in all fields, be it economic, cultural, political and self-sufficient, especially in thefield of education in general and Islamic education in particular. Important issues in Islamic religiouseducation, at least there are three important issues namely: first, about Islam Nusantara, not a few who donot accept the existence of Islam Nusantara, second, Prof.'s statement. Siti Musda Mulia, that in Indonesiathere is no need for Islamic religious education, because it is not effective in forming the character andmorality of good nation's children and third, circular letter of the Minister of Education and Culture 21 of2015 concerning the cultivation of character, whose contents are mandatory for children before starting andafter learning to pray 'a including singing Indonesia Raya song to build a child's polite attitude. Three globalissues that are becoming increasingly symptomatic today are: drugs, radicalism and pornography.